Tracks and Traces of Mont Blanc’s Itineraries: an Approach Through Wayfaring - Pierre de Potestad (Revue de Géographie Alpine)
Since the opening of the high glacial mountain to tourism, entry into this environment has been mediated by the tracks left on the snowy mantle. These tracks form a guideline that reflect the practice of wayfaring, understood as the entry into an uncertain pathway, which requires adaptation to conditions encountered and experienced. This research seeks an understanding of the pathfinding at play in recreational wayfaring in the high mountains – through the occurrence of tracks in accounts of ascents, through their figurative reproduction as traces in engravings and maps from different periods, and through reference to them in the discourse of mountain professionals. This “sense of wayfaring” articulates the evolution of itineraries and the conditions of access to the summit of Mont Blanc.